Exploring a Teacher’s Knowledge in Constructing Mathematical Lateral Thinking Problems to Teach Creativity - Shodiq, Lukman Jakfar; Juniati, Dwi; Susanah, Susanah; Rohmania, Ainnur (International Journal on Emerging Mathematics Education, 2025)
This study examined the process of constructing mathematical problems to teach creativity using the concept of lateral thinking. It employed a case study design and involved a senior junior high school mathematics teacher who has won mathematics learning innovation competitions. The teacher has understood what is meant by mathematical creativity and lateral thinking, and has proven his mathematical ability and lateral thinking ability. He was asked to create his own math problems, teach creativity, and assess students' math learning outcomes using the problems. The findings of this study highlight three key relationships: (1) the connection between mathematical content knowledge and problem-structuring ability, (2) the influence of training experience on methods for teaching creativity, and (3) the interrelationship among content knowledge, training experience, and assessment practices. These highlight the importance of integrating content knowledge and pedagogical approaches in mathematics learning to enhance creative problem-solving skills.